Deteksi Plat Nomor Kedaraan Roda Dua Menggunakan Metode Edge Detection - Erwin Dwika Putra; Dedy Abdullah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
On research done previously for segmentation of vehicle license plates have been on test cobakan method using edge detection to get the edges of characters not quite optimal. Then from the problem on this research will be focused on the detection plates two-wheeled vehicle uses a method of edge detection, where the results of this research will be resized using the technique of measurement of the confusion matrix. where in these measurements will be compared from the entire technique of edge detection, on the results of detection of vehicle license plates. edge detection method on the dispatcher of the good according to the results of the sobel operator i.e. matrix confussion and prewitt operators. With the level of accuracy of 60% while the sobel operator prewitt 63% success rate. But on each operator as explained above that still has weaknesses, namely apabil objects more than 2 objects, and when there is excess light reflection around the object that you want to detect. Keywords: Edge Detection, Confussion, Matrix Methods, Detection